Hedging and inoicing strategies to reduce exchange rate exposure : a euro-area perspective - Dohring, Bjorn. (European Economy. Economic papers, 2008)
Domestic-currency invoicing and hedging allow internationally active firms to reduce their exposure to exchange rate variations. This paper argues that domestic-currency invoicing and hedging with exchange rate derivatives allow a fairly straightforward management of transaction and translation risk. Broader economic risk (which takes into account the impact of the exchange rate on competitiveness) is by its very nature harder to manage, but the paper argues that natural hedging provides possibilities for doing so. A novelty of this paper is a survey of actual hedging strategies and techniques of large euro-area corporations. The paper finds that euro-area exporters make ample use of instruments to limit the adverse impact of euro appreciation.